MENGATASI ANAK “KIDS ZAMAN NOW”: PENGARUH MEDIA SOSIAL DI ERA GLOBALISASI TERHADAP ANAK - Agustini, Dewi; Muhammad, Abdulloh Ibnu (AL HAZIQ: Journal of Community Service, 2025)
This community service initiative focuses on strengthening digital literacy capabilities among educators and parents to effectively respond to the evolving behavioral dynamics of children in the contemporary era. This effort is driven by the powerful influence of globalization and the widespread adoption of social media, which, in the absence of appropriate supervision, pose risks of moral degradation, psychosocial issues such as Fear of Missing Out (FOMO), and cyberbullying. Conducted in Jatiroto Village, Wonogiri, the program employs participatory education methods through Digital Parenting socialization, seminars on psychological impacts, and workshops on Family Digital Contracts. Evaluation results indicate a 45% increase in participants' understanding, as measured by the comparison between pre-test and post-test scores. In conclusion, an active-collaborative mentoring model has proven more effective than authoritarian parenting approaches in mitigating the negative impacts of the digital world. Synergy between families and schools, achieved through critical digital literacy, serves as the key to shaping a generation of intelligent, productive, and ethical digital citizens.